Performing Transversally: Reimagining Shakespeare and the Critical Future - Reynolds, Bryan. author. aut Link
XVII, 319 p.
Keywords: Performing Transversally expands on Bryan Reynolds' controversial transversal theory in exciting ways while offering groundbreaking analyses of Shakespeare's plays - Hamlet , Othello , Macbeth , Taming of the Shrew , Titus Andronicus , Henry V , The Tempest , and Coriolanus - and textual, filmic, and theatrical adaptations of them. With his collaborators, Reynolds challenges traditional readings of Shakespeare, re-evaluating the critical methodologies that characterize them, in regard to issues of cultural difference, authorship, representation, agency, and iconography. Reynolds demonstrates the value of his 'investigative-expansive mode,' outlining a 'transversal poetics' that points toward a critical future that is more aware of its subjective interconnectedness with the topics and audiences it seeks to engage than is reflected in most Shakespeare criticism and literary-cultural scholarship.